Prevalence of tobacco use and its socio-demographic determinants among Saudi female school adolescents in Jeddah - Al-Otaibi, Amani Awwadh; Ibrahim, Faisal; Gyanchand Rampal, Lekhraj Rampal; Hassan, Siti Aishah; Ibrahim, Normala (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2015)
Tobacco use among females is a rising public health issue. Further insight into the smoking epidemic can be gained from studying a specific subgroup of interest within the population. Determining predictors of each tobacco smoking type is necessary for planning tobacco specific intervention programmes. The aim of this study was to determine the prevalence of ever tobacco use and its associated socio-demographic factors among Saudi female adolescents aged 12 to 19 in Jeddah. A cross-sectional analytical study was conducted among female students from intermediate and high secondary schools in Jeddah during the academic year 2012-2013. Sampling with probability proportionate to size was used to select a sample of 5,150 students from 40 schools. The data were collected using validated self-administrated questionnaire that required information on tobacco use behaviours and selected socio-demographic characteristics. A total of 5,073 students participated in this study of whom 51.6% were from intermediate grades, and 83.1% from public schools. The prevalence of ever tobacco use was 44.2% (36.2% water pipe and 30.9% cigarettes). The significant predictors of ever tobacco use were student’s age, mother’s education, family structure, residence location and monthly student’s allowance. In conclusion, ever tobacco used is highly prevalent among female adolescents in Jeddah. Designing intervention programmes aimed at preventing Saudi female adolescents from smoking should include all forms of tobacco use.